2020
DOI: 10.1080/07391102.2020.1846624
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural inhibitors against prime targets of SARS-CoV-2 using molecular docking, molecular dynamics simulation and MM-PBSA approaches

Abstract: The recently emerged COVID-19 has been declared a pandemic by the World Health Organization as to date; no therapeutic drug/vaccine is available for the treatment. Due to the lack of time and the urgency to contain the pandemic, computational screening appears to be the best tool to find a therapeutic solution. Accumulated evidence suggests that many phyto-compounds possess anti-viral activity. Therefore, we identified possible phyto-compounds that could be developed and used for COVID-19 treatment. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 74 publications
6
45
0
2
Order By: Relevance
“…The protein-ligand complexes showed a slight decrease in SASA values which indicated that in the protein-ligand complexes, the surface of the protein exposed to the aqueous solvent is reduced due to the ligand binding. Similarly, in a previous study on the remdesivir-protein system, a decrease in SASA values for protein-ligand complexes was observed [60]. The number of hydrogen bonds (H-bond) analysis indicates the strength and specificity of ligand for binding to the active site of protein as mentioned earlier [59].…”
Section: Molecular Dynamics Of Protein-ligand Complexessupporting
confidence: 58%
“…The protein-ligand complexes showed a slight decrease in SASA values which indicated that in the protein-ligand complexes, the surface of the protein exposed to the aqueous solvent is reduced due to the ligand binding. Similarly, in a previous study on the remdesivir-protein system, a decrease in SASA values for protein-ligand complexes was observed [60]. The number of hydrogen bonds (H-bond) analysis indicates the strength and specificity of ligand for binding to the active site of protein as mentioned earlier [59].…”
Section: Molecular Dynamics Of Protein-ligand Complexessupporting
confidence: 58%
“…51 The versatility of andrographolide as a SARS-CoV-2 antiviral is demonstrated by its potential to bind to several important targets at various stages of viral attachment, replication, and host-pathogen interactions. [29][30][31][32][33][34][36][37][38][39] This property may be an important advantage to any potential therapeutic agent being developed. Viral life cycle modeling studies have suggested that effective infection attenuation of repurposed drugs is more likely to be achieved when multiple segments of the viral life cycle are targeted, especially when timely administration of an antiviral in the early phases of infection is challenging in reallife settings.…”
Section: Discussion: Antiviral Evidence Against Sars-cov-2mentioning
confidence: 99%
“…59 Two papers predicted good binding of andrographolide and its derivatives with RdRp. 34,37 At present, the first and only antiviral currently approved by the U.S. FDA for the treatment of severe COVID-19, Remdesivir, is an antiviral that is thought to act through inhibition of RdRp, though its benefit in lowering mortality in COVID-19 patients remains to be investigated. 60 Remdesivir is a repurposed broad-spectrum antiviral against RNA viruses, originally developed for Ebola.…”
Section: Discussion: Antiviral Evidence Against Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations